2013
DOI: 10.1055/s-0033-1350927
|View full text |Cite
|
Sign up to set email alerts
|

Pupillenweite in Alltagssituationen

Abstract: Luminance has the strongest influence on pupil size, near fixation has hardly any influence down to 1 m. The well-known age relation of pupil size in darkness is also valid for mesopic and photopic conditions. At 3 cd/m2 it was the same as reported in darkness, at 30 cd/m2 it was less in absolute numbers, but relative as compared to young adults it was approximately the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…In line with previous laboratory findings [19–28], our data confirmed that steady-state pupil size decreases with age, even under uncontrolled real-world conditions. In addition, our exploratory results replicate that the effect is stronger in dim compared to bright light conditions [13, 24, 28, 29, 77]. Perhaps the most compelling findings are the consistent linear regression parameters between our data and the laboratory data presented in Figure 2 by Winn et al in 1994 [28].…”
Section: Discussionsupporting
confidence: 84%
“…In line with previous laboratory findings [19–28], our data confirmed that steady-state pupil size decreases with age, even under uncontrolled real-world conditions. In addition, our exploratory results replicate that the effect is stronger in dim compared to bright light conditions [13, 24, 28, 29, 77]. Perhaps the most compelling findings are the consistent linear regression parameters between our data and the laboratory data presented in Figure 2 by Winn et al in 1994 [28].…”
Section: Discussionsupporting
confidence: 84%
“…The reduction in baseline pupil diameter from the youngest to the oldest age group of 1.45 mm in photCPC and 1.53 mm in scotCPC is in accordance with previous findings of an average of approximately 0.04 mm decrease per year under weak illumination. 27 , 28 This validates our method as precise enough to reproduce such expected effects and serves as a proof-of-concept for a reliable evaluation of pupillary responses and possible influencing factors. It additionally emphasizes the importance of the normalization of the pupillary constriction amplitude to the baseline pupil diameter in PLR evaluation.…”
Section: Discussionsupporting
confidence: 64%
“…1 Heine et al found that the mesopic pupil size decreased by 0.42 mm per decade in a population of 206 volunteers aged between 18 and 72 years without disorders influencing the pupil. 10 Unlike the well-known bifocal Restor IOL (Alcon, Fort Worth, USA), which shares the same AcrySof IQ platform, the design of the PanOptix does not feature apodization; a varying step height of the diffractive rings with the pupil size. The absence of apodization ensures that the light energy allocation to the three foci is independent of the pupil.…”
Section: Discussionmentioning
confidence: 99%
“…larger pupil diameter, increased healing reaction or incomplete eye growth, need to be considered when using lenses with these optics in pediatric cases. 9 , 10 Furthermore, the possibility of amblyopia should be taken into account. Since multifocal IOLs split the incoming light energy on different foci, a loss in contrast sensitivity might occur.…”
Section: Introductionmentioning
confidence: 99%